CRISPR/Cas9-mediated gene mutation of EcIAG leads to sex reversal in the male ridgetail white prawn Exopalaemon carinicauda - Miao, Miao; Li, Shihao; Yuan, Jianbo; Liu, Peipei; Fang, Xiaochen; Zhang, Chengsong; Zhang, Xiaojun; Li, Fuhua (Frontiers in Endocrinology, 2023)
In the culture of crustaceans, most species show sexual dimorphism. Monosex culture is an effective approach to achieve high yield and economic value, especially for decapods of high value. Previous studies have developed some sex control strategies such as manual segregation, manipulation of male androgenic gland and knockdown of the male sexual differentiation switch gene encoding insulin-like androgenic gland hormone (IAG) in decapods. However, these methods could not generate hereditable changes. Genetic manipulation to achieve sex reversal individuals is absent up to now. In the present study, the gene encoding IAG (EcIAG) was identified in the ridgetail white prawn Exopalaemon carinicauda. Sequence analysis showed that EcIAG encoded conserved amino acid structure like IAGs in other decapod species. CRISPR/Cas9-mediated genome editing technology was used to knock out EcIAG. Two sgRNAs targeting the second exon of EcIAG were designed and microinjected into the prawn zygotes or the embryos at the first cleavage with commercial Cas9 protein. EcIAG in three genetic males was knocked out in both chromosome sets, which successfully generated sex reversal and phenotypic female characters. The results suggest that CRISPR/Cas9-mediated genome editing technology is an effective way to develop sex manipulation technology and contribute to monosex aquaculture in crustaceans.